Links between copper and cholesterol in Alzheimer's disease - Hung, Ya Hui; Bush, Ashley I.; La Fontaine, Sharon (Frontiers in Physiology, 2013)
Altered copper homeostasis and hypercholesterolemia have been identified independently as risk factors for Alzheimer’s disease (AD). Abnormal copper and cholesterol metabolism are implicated in the genesis of amyloid plaques and neurofibrillary tangles (NFT), which are two key pathological signatures of AD. Amyloidogenic processing of a sub-population of amyloid precursor protein (APP) that produces Aβ occurs in cholesterol-rich lipid rafts in copper deficient AD brains. Co-localization of Aβ and a paradoxical high concentration of copper in lipid rafts fosters the formation of neurotoxic Aβ:copper complexes. These complexes can catalytically oxidize cholesterol to generate H2O2, oxysterols and other lipid peroxidation products that accumulate in brains of AD cases and transgenic mouse models. Tau, the core protein component of NFTs, is sensitive to interactions with copper and cholesterol, which trigger a cascade of hyperphosphorylation and aggregation preceding the generation of NFTs. Here we present an overview of copper and cholesterol metabolism in the brain, and how their integrated failure contributes to development of AD.